Improving Experience in Personal Social Systems through Family Constellation Seminars: Results of a Randomized Controlled Trial. Issue 2 (19th November 2013) - Hunger, Christina; Bornhäuser, Annette; Link, Leoni; Schweitzer, Jochen; Weinhold, Jan
<x xml:space="preserve">Abstract</x> This study examined the efficacy of family constellation seminars (FCSs) on individuals' experience in their personal social systems, especially the experience of belonging, autonomy, accord, and confidence. We conducted a single‐blind, stratified and balanced, randomized controlled trial. Participants were 208 adults (M = 48 years, SD = 10, 79% women) who were randomly allocated either to the intervention group (3‐day FCSs; 64 active participants, 40 observing participants) or to the wait‐list group (64 active participants, 40 observing participants). Change was measured short‐term (2‐week and 4‐month follow‐up) using the Experience In Social Systems Questionnaire, personal domain (EXIS.pers). EXIS.pers is a new outcome measure being applied for the first time in evaluation research. In addition, we used interpersonal scales derived from established measures (Outcome Questionnaire, OQ‐45; Tool for the Evaluation of the Psychotherapeutic Progress, FEP). The average person in the intervention group showed improved experience in personal social systems, as compared with approximately 73% of the wait‐list group after 2 weeks (total score: Cohen's d = .61, p = .000) and 69% of the wait‐list group after 4 months (total score: d = .53, p = .000). The results were confirmed in per‐protocol analyses (n = 191) by the results of the EXIS.pers dimensions (Belonging, Autonomy, Accord, and Confidence) and the interpersonal scales derived from the OQ‐45 and FEP. No adverse events were reported. This RCT provides first evidence that FCSs tend to positively influence participants' experience in their social systems.